A time-series analysis on the impact of the antiretroviral treatment program on the burden of hospitalization for culture-confirmed Mycobacterium tuberculosis in Sowetan children - Dangor, Ziyaad (My University, 2013)
Introduction: Highly active antiretroviral treatment (HAART) programs in heavily HIV-TB burdened countries may reduce the risk of TB in children directly by improving the immune system of HIV-infected children; and indirectly by reducing the force of transmission from the adult population. The incidence of childhood TB is a sentinel measure of the control of infectious adult TB cases in the community. Objective: We evaluated the impact that scaling-up of the HAART program in Soweto had on the incidence of hospitalization for culture-confirmed TB in children. Methods: The study was undertaken in Soweto, where the prevalence of HIV was 4-5% in children between 2005 and 2009. The estimated HAART coverage increased from 43% in 2005 to 84% by 2009 in children with HIV/AIDS. Hospitalized cases of culture-confirmed TB in children 3 months to 14 years of age were identified through laboratory and clinical electronic databases. Results: Overall, the incidence (per 100 000) of hospitalization for culture-confirmed TB declined by 58% (95%CI 49.3-65.2) from 2005 (71.4) compared to 2008-9 (30.0); p<0.0001. This included a 67% (95%CI 58.5-74.8) reduction in incidence among HIV-infected children from 2005 (1 601) compared to 2008-9 (517; p<0.0001). v In addition, a 33% reduction was observed in HIV-uninfected children (incidence 19.3 vs 12.9; p=0.016). Fifty-six percent of TB episodes, across all study periods, occurred in HIV-infected children who were mainly (76%) severely immunocompromised. Conclusions: Up-scaling of the HAART program in South Africa has been associated with decline in the incidence of culture-confirmed TB, more so in HIV-infected than HIV-uninfected children. Severely immunocompromised HIV-infected children, however, need to be identified and targeted with HAART and other strategies to further reduce the burden of TB in this group.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment for the degree Masters of Medicine in Paediatrics (MMed) Johannesburg 2012
Keywords: Antiretroviral Therapy, Highly Active; HIV; Tuberculosis